Extrahepatic portal vein obstruction in children of the first year of life: diagnostic and treatment approaches - O.S. Godik; D.S. Diehtiarova; O.I. Kvilinska (Український журнал Перинатологія і педіатрія)
Extrahepatic portal vein obstruction (EHPVO) is an important cause of symptomatic portal hypertension (PH) in pediatric population. PH may lead to serious complications including variceal bleeding and hypersplenism. Literature data on infants under 12 months old with EHPVO is poor.